Experimental Testing and Numerical Simulation of Recycled Concrete Aggregate in a Concrete Mix - Bini Neupane; Kameshwar Sahani; Shyam Sundar Khadka (International Journal of Concrete Structures and Materials)
Abstract This study focuses on exploring the potential of utilizing demolished concrete and promoting sustainable practices through the use of recycled concrete aggregate (RCA) as a substitute for natural aggregates, particularly in the context of Nepal. The region’s susceptibility to frequent earthquakes results in significant volumes of concrete rubble, posing challenges in waste disposal. To address this issue and mitigate resource depletion, the research focuses on concrete recycling. By conducting a thorough analysis of mechanical properties, crack patterns, strength variations, and specific gravity evaluations across different RCA compositions, the study emphasizes the ongoing endeavors toward sustainable concrete practices. A comparative examination of test results involving varying percentages of coarse recycled aggregate content (0%, 25%, 50%, 75%, and 100%) denoted as R0, R25, R50, R75 and R100, respectively, provides insights into the performance of different mixes. The compressive strength of cube for R25 increased by 20.13%, while R50 and R75 showed gains of 8.08% and 1.28%, respectively, while cylinder showed an increase of 25.86%, 18.88%, 9.54% and 2.65% for R25, R50, R75 and R100, respectively, compared to R0 concrete mix when tested at 28 days of curing. Tensile strength of concrete cylinder also improved, with R25 showing an 18.52% increase and R50 showing a 9.26% increase. Additionally, the RCA increased the flexural strength, with R25 leading with a 5% increase and R50 following with a 1.66% increase at 28 days of testing. The inclusion of numerical analysis in ABAQUS CAE using the Kent and Park Model serves to reinforce and support the experimental findings, establishing the credibility of both approaches. In essence, the study strongly advocates for the integration of recycled aggregate in concrete as a means to foster sustainable development and environmentally friendly construction methods.